Analisis Kinerja Keuangan Pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Pulau Morotai - Jamiludin Hasan; Rusman Soleman; Hartaty Hadady (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this research is to determine and analyze the financial performance of PDAM Kabupaten Pulau Morotai using financial ratio analysis based on liquidity ratios, activity ratios, solvency ratios, and profitability ratios. In addition to the financial ratio analysis, the researcher interviewed several key informants. The balance sheet and income statement PDAM are secondary data, while interviews with informants are primary data. The findings of the financial ratio analysis research at PDAM Pulau Morotai Regency are based on liquidity ratios seen from the Current Ratio in 2017-2019; the company's condition is in a deficit, the Fast Ratio in 2015-2019 is in good condition, and the cash ratio is relatively poor. When viewed from asset turnover ratio and total asset turnover, the company's condition in 2015-2019 was not good because the turnover obtained was only one time. When viewed from the Debt Ratio (debt ratio), the company's condition in 2015-2019 is quite good because it can pay all of its debts. The company's capital is greater than the company's debt, primarily the company's debt is 20%, and the company's capital is 80%. When viewed from the Operating Income in 2015-2019, the financial ratio indicates that the company's condition is not stable because the profit generated is a deficit. ROA from 2015 to 2019. The company's situation is problematic because risks offset the profits generated. ROE is also in a horrible state. According to the findings of this study, PDAM Morotai Island Regency is less stable in financial performance when viewed from the profitability ratios, risky when viewed from the company's activity ratio, average in financial performance when viewed from the company's solvency ratio, and finally good in financial performance when viewed from the PDAM Morotai Island Regency's PDAM Morotai Island Regency's PDAM Morotai Island Regency's PDAM.